Étude de l’effet d’incorporation des feuilles de Rosmarinus officinalis L (Romarin) sur la qualité des olives de table de cultivar SIGOISE élaborée selon le style californien - MEKDOUR, Mohammed (My University, 2022)
This study aims to follow the effect of the addition of the leaves of Rosmarinus officinalis L., (rosemary) harvested in the region of Naama in the south of Algeria on the antioxidant activity and the organoleptic quality of black table olives in brine. of the Sigoise variety after 30 days of storage in the atmosphere. Three batches of three boxes containing 400 g of olives were made up at the end of production by the Californian style. Rosemary leaves were added to the olive samples from each batch at 0, 10% and 15%, respectively. The physicochemical analyzes were carried out in triplicate tests. The parametric results were processed statistically by an analysis of variance supplemented by a comparison of the means; while the nonparametric data were treated by the Friedman test. The addition of rosemary leaves markedly increased the phenolic compound and flavonoid contents of table olives during their storage. After 30 days of storage in the atmosphere, the physico-chemical parameters of the olive pulp showed a remarkable decrease (p<0.01) in pH and a notable increase in lactic acidity depending on the addition of rosemary.; while the fat, ash and moisture levels are acceptable and remain within normal values. The peroxide index, the malonaldehyde level and the IC50 values of olive oil preserved in rosemary decreased significantly (p<0.01) compared to the control; unlike the inhibition rates at DPPH, as well as the scavenger power which have clearly increased. The addition of rosemary therefore seems to best preserve the oxidation and the quality of the oil of the table olives. Finally, the sensory analysis revealed that the table olives preserved with the addition of rosemary leaves were the most appreciated by the panelists.
Keywords: Black table olives; Sigoise; Quality; Rosmarinus officinlis L; Conservation; Antioxidant